On the Equivalence between Two Fixed Point Theorems for Concave-Type Operators. (12th July 2021) - Jleli, Mohamed; Samet, Bessem
Abstract : In this note, we prove the equivalence between a fixed point theorem for φ –h, e –concave operators and a previous one for generalized concave operators.